Rare disease, twin girl with Dopa Responsive Dystonia suspicious Segawa disease in Indonesia - Hanifah, Nur; Gunawan, Prastiya Indra; Noviandi, Riza; Samosir, Sunny Mariana (Acta Biomedica Atenei Parmensis, 2024)
.